2016
DOI: 10.1021/jacs.5b10819
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for a 3d10 Ground State Electronic Configuration and Ligand Field Inversion in [Cu(CF3)4]1–

Abstract: The contested electronic structure of [Cu(CF3)4](1-) is investigated with UV/visible/near IR spectroscopy, Cu K-edge X-ray absorption spectroscopy, and 1s2p resonant inelastic X-ray scattering. These data, supported by density functional theory, multiplet theory, and multireference calculations, support a ground state electronic configuration in which the lowest unoccupied orbital is of predominantly trifluoromethyl character. The consensus 3d(10) configuration features an inverted ligand field in which all fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 116 publications
(167 citation statements)
references
References 72 publications
(91 reference statements)
7
150
0
Order By: Relevance
“…Whereas the heaviest [Au(CF 3 ) 4 ] − derivative arises little suspicion, the oxidation state of the lightest [Cu(CF 3 ) 4 ] − derivative has been much debated . In fact, despite considerable effort to ascertain the bonding scheme of this organocopper derivative, this question still remains unanswered.…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…Whereas the heaviest [Au(CF 3 ) 4 ] − derivative arises little suspicion, the oxidation state of the lightest [Cu(CF 3 ) 4 ] − derivative has been much debated . In fact, despite considerable effort to ascertain the bonding scheme of this organocopper derivative, this question still remains unanswered.…”
Section: Methodsmentioning
confidence: 55%
“…This bonding scheme has been confirmed recently, but with some emphasis put on the covalent character of the Cu−C bond, as already pointed out by Kaupp and von Schnering . Recent experimental spectroscopic measurements on [Cu(CF 3 ) 4 ] − salts also gave apparently conflicting results . Following X‐ray electron density studies, the estimated atomic charge on the copper atom is close to +1 .…”
Section: Methodsmentioning
confidence: 99%
“…The[ (Py) 2 Ni II (CF 3 ) 2 ]c omplex 1 instantaneously reacts with starting complex 3 in ac omproportionation reaction to form 2/2·Py. Thei nvolvement of CCF 3 radicals in the ArÀCF 3 coupling with Ni IV species 3 has thus been demonstrated unambiguously for the first time.Itistobenoted that Lancaster and co-workers very recently proposed that the Ni IV CF 3 complexes of type III reported by Sanford and coworkers may be an ew case study for "inverted" ligand field, [17] and that III should be prone to eliminate CCF 3 radicals. Tw op ossibilities were envisaged.…”
Section: Zuschriftenmentioning
confidence: 99%
“…After 24 h, the yield of the product of DCB trifluoromethylation was only 20 %, and the product of CCF 3 radical addition to the nitrone was also detected by EPR analysis (Figure S9). Thei nvolvement of CCF 3 radicals in the ArÀCF 3 coupling with Ni IV species 3 has thus been demonstrated unambiguously for the first time.Itistobenoted that Lancaster and co-workers very recently proposed that the Ni IV CF 3 complexes of type III reported by Sanford and coworkers may be an ew case study for "inverted" ligand field, [17] and that III should be prone to eliminate CCF 3 radicals. [18] In conclusion, we have devised af acile route for the synthesis of the unique Ni IV complex [(Py) 2 Ni IV F 2 (CF 3 ) 2 ](3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[7] In 2015, Grushin et al reported bpyCu(CF 3 ) 3 and related complexes that are bench-stable and easy to prepare. [9] Consequently,s uch copper complexes are more accurately described, and spectroscopically observed, [10] as Cu I ,which has significant implications for reactivity. [9] Consequently,s uch copper complexes are more accurately described, and spectroscopically observed, [10] as Cu I ,which has significant implications for reactivity.…”
mentioning
confidence: 99%